Decellularized Tracheal Extracellular Matrix Supports Epithelial Migration, Differentiation, and Function - Kutten, Johannes C. (Tissue Eng Part A, 2015)
Tracheal loss is a source of significant morbidity for affected patients with no acceptable solution. Interest in engineering tracheal transplants has created a demand for small animal models of orthotopic tracheal transplantation. Here, we examine the use of a decellularized graft in a murine model of tracheal replacement. Fresh or decellularized tracheas harvested from age-matched female donor C57BL/6 mice were transplanted into syngeneic recipients. Tracheas were decellularized using repeated washes of water, 3% Triton X-100, and 3 M NaCl under cyclic pressure changes, followed by disinfection with 0.1% peracetic acid/4% ethanol, and terminal sterilization by gamma irradiation. Tracheas were explanted for immunolabeling at 1, 4, and 8 weeks following surgery. Video microscopy and computed tomography were performed to assess function and structure. Decellularized grafts supported complete reepithelialization by 8 weeks and motile cilia were observed. Cartilaginous portions of the trachea were maintained in mice receiving fresh transplants, but repopulation of the cartilage was not seen in mice receiving decellularized transplants. We observed superior postsurgical survival, weight gain, and ciliary function in mice receiving fresh transplants compared with those receiving decellularized transplants. The murine orthotopic tracheal transplant provides an appropriate model to assess the repopulation and functional regeneration of decellularized tracheal grafts.